PERFORMANCE ANALYSIS OF SUPERVISORY CONSULTANTS ON PROJECTS IN THE HOUSING AND SETTLEMENT AREAS OF EAST JAVA PROVINCE - Rahadian, Deni; Koespiadi, Koespiadi; Oetomo, Wateno (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2023)
The Supervisory Consultant is the party assigned by the project owner to realize the planned planning results according to the development of good settlement infrastructure facilities and utilities. The government, especially in the PRKP Division of East Java Province, collaborates with service providers, one of which is a supervisory consultant, in this case encouraging supervisory consultants to increase understanding of customer satisfaction. This research has several objectives, namely identifying variables of project management performance of PRKP activities in East Java Province; measuring the level of customer satisfaction from the project management performance of PRKP activities in East Java Province. The research stages taken in this study, namely Research background, Formulation of problems and research objectives, Literature study, Preliminary survey, Data collection, Data testing, Data analysis. The analysis method used is the customer satisfaction index method. The data is processed using the MS.Excel and SPSS programs. The results of the analysis with the customer satisfaction index show a CSI value of 63.55% which means satisfied. which is low and needs to be improved.